Pharmacy collected medication histories in an observation unit. (11th August 2015) - Procopio, Gabrielle L; Faley, Brian; Wynd, Michael A; Finefrock, Douglas; Kobayashi, Michelle; Feldman, Joseph
Background: Clear processes to facilitate medication reconciliation in a hospital setting are still undefined. The observation unit allows for a high patient turnover rate, where obtaining accurate medication histories is critical. Objectives: The objective of this study was to assess the ability of pharmacists and student pharmacists to identify discrepancies in medication histories obtained at triage in observation patients. Methods: Pharmacists and student pharmacists obtained a medication history for each patient placed in observation status. Patients were excluded if they were unable to provide a medication history and family, caregiver, or community pharmacy was also unable to provide the history. A comparison was made between triage and pharmacy collected medication histories to identify discrepancies. Results: A total of 501 medications histories were collected, accounting for 3213 medication records. There were 1176 (37%) matched medication records and 1467 discrepancies identified, including 808 (55%) omissions, 296 (20.2%) wrong frequency, 278 (19%) wrong dose, 51 (3.5%) discontinued, and 34 (2.3%) wrong medication. There was an average of 2.9 discrepancies per patient profile. In all, 76 (15%) of the profiles were matched. The median time to obtain a medication history was 4 min (range: 1–48 min). Conclusion: Pharmacy collected medication histories in an observation unit identify discrepancies that can be reconciled by the interdisciplinary team.